Controlled-strain oedometer tests on Nong Ngoo Hao clay - Dang, Huynh-anh; Brand, E.W.; Moh, Za-Chieh; Richardson, A.M.; Government of the Federal Republic of Germany (Bangkok : Asian Institute of Technology, 1975)
This thesis was concerned with the application of controlled-strain consolidation tests to Soft and Stiff Bangkok Clay. An extensive program of such tests was conducted to measure the effects of rate of strain; and to compare the results obtained for deduced compressibility and rate of compression with those determined by conventional controlled-stress tests. It was found that the rate of strain adopted for the controlled strain tests generally affected the shape of the stress-strain curve, the slower strain rate resulting in more abrupt changes in slope at the critical pressure and in the transition range. The critical pressure was very well defined by the slow rate of strain test and the stress-strain curve assumed the shape for a sensitive clay. The stress-strain curve would not be as well defined by a controlled-stress test. The results from the two kinds of test were very comparable, and it is thought that the controlled-strain test has several advantages, not least the greatly reduced total time for each consolidation test.
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Engineering at the Asian Institute of Technology, Bangkok, Thailand .
Thesis (M.Eng.) - Asian Institute of Technology, 1975
Keywords: Strains and stresses; Soil consolidation; Clay -- Thailand -- Nong Ngoo Hao